Analisis Optimalisasi Efiensi Operasional Bank BNI Berdasarkan Rasio Biaya Dana Pada Tahun 2019-2021 - M.Arief Safi’i; Ratna Ayu Wijayanti; Riki Zogik Firmansyah; Renny Oktafia (CV. ALIM'SPUBLISHING, 2024)
This research evaluates and optimizes the operational efficiency of Bank Negara Indonesia (BNI) during the 2020-2023 period with a focus on the cost of funds ratio. Using a quantitative approach and qualitative interpretation, this research analyzes BNI financial data to identify trends and factors that influence fund expense ratios. The results provide insight into BNI's performance compared to industry standards and competitors. It is hoped that the recommendations from this research can help BNI management improve operational efficiency, support competitiveness in the banking industry, and make a positive contribution to the national economy.